Comparing social bee and wasp diversity in different agricultural landscapes using pan traps - Roslan, Fatin Afiqah (2018)
Forest conversion into agricultural lands has become a global concern due to habitat degradation that reduces overall biodiversity specifically insects. Insects responsed to agricultural land use, however, may vary between different management such as monoculture and polyculture systems. In this study, social bees and wasps (Insecta: Hymenoptera) were compared between different agricultural landscapes namely; polyculture orchard, monoculture rubber and monoculture oil palm plantations. The study was carried out in Kampung Sungai Lalah, Pedas, Negeri Sembilan for 28 days from January to February 2018. Social bees and wasps were sampled using yellow pan trap at all agricultural sites (total sampling point = 45). From the results, a total of 1045 individuals social bees and wasps belonging to eight families were recorded. Polyculture orchard showed the greatest abundance of social bees and wasps followed by monoculture oil palm and monoculture rubber plantations. Surprisingly, all agricultural sites recorded similar number of social bees and wasps family. However, family composition differed between polyculture and monoculture landscapes where Apidae was only recorded in orchard while Braconidae was only recorded in rubber and oil palm plantations. Polyculture orchard also showed significantly greater vegetation cover and relative humidity that may provide suitable habitat conditions for social bees and wasps. The findings proved that habitat heterogeneity in polyculture systems may support greater abundance of social bees and wasps compared to monoculture plantations. Social bee and wasp abundance and diversity of in agricultural landscape may indicate enhance local diversity as this particular insect group providing important ecosystem services such as pollination and biological control. Thus, polyculture systems should be established in agricultural landscape for improved insect conservation and ecosystem services.